RP-UHPLC-UV-ESI-MS/MS analysis of LPMO generated C4-oxidized gluco-oligosaccharides after non-reductive labeling with 2-aminobenzamide. (7th August 2017) - Frommhagen, Matthias; van Erven, Gijs; Sanders, Mark; van Berkel, Willem J.H.; Kabel, Mirjam A.; Gruppen, Harry
Abstract: Lytic polysaccharide monooxygenases (LPMOs) are able to cleave recalcitrant polysaccharides, such as cellulose, by oxidizing the C1 and/or C4 atoms. The analysis of the resulting products requires a variety of analytical techniques. Up to now, these techniques mainly focused on the identification of non-oxidized and C1-oxidized oligosaccharides. The analysis of C4-oxidized gluco-oligosaccharides is mostly performed by using high pressure anion exchange chromatography (HPAEC). However, the alkaline conditions used during HPAEC analysis lead to tautomerization of C4-oxidized gluco-oligosaccharides, which limits the use of this technique. Here, we describe the use of reverse phase-ultra high performance liquid chromatography (RP-UHPLC) in combination with non-reductive 2-aminobenzamide (2-AB) labeling. Non-reductive 2-AB labeling enabled separation of C4-oxidized gluco-oligosaccharides from their non-oxidized counterparts. Moreover, RP-UHPLC does not require buffered mobile phases, which reduce mass spectrometry (MS) sensitivity. The latter is seen as an advantage over other techniques such as hydrophilic interaction liquid chromatography and porous graphitized carbon coupled to MS. RP-UHPLC coupled to UV detection and mass spectrometry allowed the identification of both labeled non-oxidized and C4-oxidized oligosaccharides. Non-reductive labeling kept the ketone at the C4-position of LPMO oxidized oligosaccharides intact, while selective reducing agents such as sodium triacetoxyborohydride (STAB) reduced this ketone group. Our results show that RP-UHPLC-UV-ESI-MS in combination with non-reductively 2-AB labeling is a suitable technique for the separation and identification of LPMO-generated C4-oxidized gluco-oligosaccharides. Graphical abstract: Highlights: RP-UHPLC in combination with non-reductive 2-AB labeling for LPMO analysis. Non-reductive 2-AB labeling enabled separation of C4-oxidized gluco-oligosaccharides. RP-UHPLC-MS identification of labeled non- and C4-oxidized gluco-oligosaccharides.